X‐ray computed tomography evaluations of additive manufactured multimaterial composites. (4th June 2021) - Curto, M.; Kao, A. P.; Keeble, W.; Tozzi, G.; Barber, A. H.
Abstract : Abstract: Additive Manufacturing (AM) often produces complex engineered structures by precisely distributing materials in a layer‐by‐layer fashion. Multimaterial AM is a particularly flexible technique able to combine a range of hard and soft materials to produce designed composites. Critically, the design of AM multimaterial structures requires the development of precise three‐dimensional (3D) computed aided design (CAD) files. While such digital design is heavily used, techniques able to validate the physically manufactured composite against the digital design from which it is generated are lacking for AM, especially as any evaluations must be able to distinguish material variation across the 3D space. Nowadays, there is a growing interest in volumetric tools that can provide topological information hidden by the surface of shaped materials. So far, technologies such as Optical microscopy (OM), Scanning Electron Microscopy (SEM), and Coordinate Measuring Machine (CMM) have paved the way into the metrology field to measure the external geometry of physical objects. Currently, alongside conventional metrology tools, X‐ray computed tomography (XCT) is emerging to measure the subsurface of the objects but maintaining the integrity of the probed samples. Thereby, the volumetric nature of the XCT investigations and its associated imaging techniques, ensure 3D quantitative measurements comparable to the output data from 2D metrology tools, but above all, supply the missing subsurface description for an exhaustive metrology study. The reward associated with XCT applied to multimaterial AM is a map reflecting the fabricated distribution of materials following CAD, with the benefits of better understanding the mechanical interplay within phases, hence, describing the hidden processes as well as the changes in phases due to a range of mechanical or chemical phenomena. In this study, a nondestructive approach using X‐ray computed tomography (XCT) is used to fully evaluate the 3D distribution of multimaterials from an AM process. Specifically, two diverse hard and soft materials are alternatively produced in the form of a fibre embedded in a matrix via ink‐jet printing. XCT coupled with imaging evaluation were able to distinguish between the differing materials and, importantly, to demonstrate a reduction in the expected fabricated volumes when compared to the respective CAD designs. Lay description: Additive Manufacturing (AM) has recently become important in producing complex engineered structures. Using 3D CAD files and/or reconstructed data sets from imaging, hard and soft materials are manufactured independently or in combination, according to geometrical features and shapes in the input data. However, the evaluation of the resultant manufactured parts in comparison with the original 3D drawing is currently lacking. In this sense, X‐ray computed tomography (XCT) provides an important metrology tool for mono and multimaterial AM. In this work a volumetric metrology investigation is proposed using higher resolution XCT to provide 3D information comparable to that of the 3D CAD drawings. A commercial high‐resolution multijetting material printer (ProJet 5500X, 3D Systems, USA) is used to manufacture single fibre composites, through a complementary deposition of photo sensible polymers. Hard and soft plastics are produced using a UV curable step, resulting in materials of similar attenuation under an X‐ray probe. A critical aim of the evaluations is the potential for XCT to distinguish between different UV curable 3D printing materials.